2019
DOI: 10.3389/fmicb.2019.01188
|View full text |Cite
|
Sign up to set email alerts
|

Filamentous Non-albicans Candida Species Adhere to Candida albicans and Benefit From Dual Biofilm Growth

Abstract: Non- albicans Candida species (NACS) are often isolated along with Candida albicans in cases of oropharyngeal candidiasis. C. albicans readily forms biofilms in conjunction with other oral microbiota including both bacteria and yeast. Adhesion between species is important to the establishment of these mixed biofilms, but interactions between C. albicans and many NACS are not well-characterized. We adapted a real-time fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 62 publications
0
33
0
Order By: Relevance
“…However, under certain conditions, especially those related to immune suppression or even in neonates or elderly, there is an increase in Candida carriage in the oral cavity that ultimately leads to the development of opportunistic mucosal infections ( Nicolatou-Galitis et al, 2001 ; Bertolini and Dongari-Bagtzoglou, 2019 ). In this context, many studies have reported inter-kingdom Candida -bacterial interactions in the oral cavity, as well as Candida-Candida interactions and their role in oral diseases, especially at the mucosal sites ( Baena-Monroy et al, 2005 ; Thein et al, 2009 ; Martins et al, 2016 ; Negrini et al, 2019 ; Pathirana et al, 2019 ; Rodrigues et al, 2019 ). Moreover, Paracoccidioides spp.…”
Section: Discussionmentioning
confidence: 99%
“…However, under certain conditions, especially those related to immune suppression or even in neonates or elderly, there is an increase in Candida carriage in the oral cavity that ultimately leads to the development of opportunistic mucosal infections ( Nicolatou-Galitis et al, 2001 ; Bertolini and Dongari-Bagtzoglou, 2019 ). In this context, many studies have reported inter-kingdom Candida -bacterial interactions in the oral cavity, as well as Candida-Candida interactions and their role in oral diseases, especially at the mucosal sites ( Baena-Monroy et al, 2005 ; Thein et al, 2009 ; Martins et al, 2016 ; Negrini et al, 2019 ; Pathirana et al, 2019 ; Rodrigues et al, 2019 ). Moreover, Paracoccidioides spp.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to forming polymicrobial biofilms with bacteria, C.albicans also establishes mixed-species biofilms with other Candida (Pathirana et al, 2019;Tati et al, 2016;Vipulanandan et al, 2018). One common clinical example of this is oropharyngeal candidiasis, which often involves multiple Candida species (Redding, 2001).…”
Section: Host Responses To Candida In Mixed-species Biofilmsmentioning
confidence: 99%
“…Co-culture of the organisms lead to upregulation of C. glabrata cell surface proteins that allow for adhesion to C. albicans hyphae ( Tati et al, 2016 ). Additional examples of species involved in mixed-species biofilms include C. dubliniensis and C. tropicalis , both of which appear to adhere to C. albicans and exhibit a growth benefit ( Pathirana et al, 2019 ). When co-cultured together, these species form biofilms that achieve higher surface coverage.…”
Section: Host Responses To Candida In Mixed-speciementioning
confidence: 99%
“…Recently, it was reported that C. glabrata in some clinical isolates did not show NETs formation, which may be correlated with the high mortality rates in infected patients [16]. C. tropicalis is capable of adhesion with C. albicans and a dual culture biofilm of C. albicans with C. tropicalis offers a growth advantage for C. tropicalis [17]. C. tropicalis also has reduced susceptibility to azoles [11].…”
Section: Introductionmentioning
confidence: 99%